Analisis Kinerja Keuangan Koperasi Sawit Jaya Dalam Usaha Pemberdayaan Masyarakat (Studi Kasus Uuo Petapahan Makmur Sejahtera Desa Petapahan Kecamatan Tapung Kabupaten Kampar) - Pramono, Agung; Putri, Dini Amalia; Rasihen, Yogy; Kurniaty, Tri (Universitas Pahlawan Tuanku Tambusai, 2025)
Village Unit Cooperatives (KUD) in the oil palm plantation sector are rooted in the need to improve the welfare of smallholders through efficient and sustainable collective management. The Petapahan Makmur Sejahtera Autonomous Business Unit (UUO), part of the Sawit Jaya Village Unit Cooperative (KUD), has a strategic role in supporting the empowerment of oil palm farmers in Petapahan Village, Tapung District, Kampar Regency. This study aims to analyze the financial performance of UUO Petapahan Makmur Sejahtera in the 2020-2023 period using a financial ratio analysis approach, which includes liquidity, solvency, profitability, and activity ratios. The results of the study indicate that UUO's liquidity is in very good condition, but idle funds indicate suboptimal management. The solvency ratio shows a high level of dependence on long-term debt, especially from replanting funds, which results in an inadequate solvency condition. Profitability shows inadequate results, with ROI and ROE ratios below ideal standards. The activity ratio also indicates the efficiency of resource use that needs to be improved. Based on the analysis results, it is recommended that UUO optimize fund management for productive investment, improve operational efficiency, and diversify businesses to reduce dependence on one sector. In addition, increasing transparency and professionalism in cooperative management is expected to increase member trust and support the sustainability of cooperative operations.